Tinjauan Hukum atas Penggunaan Cryptocurrency atau Mata Uang Kripto Sebagai Alat Pembayaran di Indonesia - Azmi , Dzakwan; Lestari, Ahdiana Yuni (Proceeding Legal Symposium, 2023)
The presence of crypto coins as a new thing in society certainly requires a legal attitude. The rapid development of crypto coins makes many people believe that crypto coins will become a means of payment in the future. This study aims to find out the arrangements regarding payment instruments in Indonesia and the legal consequences if crypto coins are used as payment instruments in Indonesia. this writing uses Normative Legal Research, namely research with assessment through literature studies based on primary and secondary legal materials. The problem approach used is the statutory approach and the conceptual approach. The results of this study show concretely that crypto coins are illegitimate means of payment. The use of crypto coins as a means of payment in Indonesia is not in accordance with the law and is an act that is against the law so that it can lead to legal consequences. Crypto coins do not have a legal basis to be used as a means of payment in Indonesia. Payments using crypto coins which are prohibited by law are considered illegal payments so they can be subject to sanctions